AWARENESS AND KNOWLEDGE ABOUT DENTAL BIOMEDICAL WASTE MANAGEMENT AMONG HEALTH CARE WORKERS OF GUJARAT, INDIA - VYAS, MEGHA L; BHARWANI, ASHIT; BAXI, HARSH; PATHAK, SHIVANG (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of this study was to assess the knowledge, attitudes, and practices related to medical waste management (MWM) among healthcare workers in clinics. Methods: The introduced study was an enlightening cross-sectional study. A self-directed poll was intended to record age, sex, kind of training, long stretches of training, extra preparation, information and practices on risky dental waste and information, and practice of security measures against cross-disease. The review populace included dental specialists and other medical services laborers of our emergency clinic. No data were accessible about the information on dental specialists with respect to the board of dangerous waste. From each state on India, Health-care laborers were chosen haphazardly from the rundown. A self-controlled poll was asked to the 200 medical care laborers. Overall response rate was 63% (n=200). Identity of the respondents was kept confidential. Results: A total of 200 questionnaires were distributed. Returns were 150 questionnaires with 55% males and 45% females. Only 42% of respondents were aware of the existence of guidelines of waste management. From this study, it was found that majority of study populations were not aware about the management of biomedical waste. Conclusion: Our study showed that although the attitude toward biomedical waste management was highly positive among students and they understood the importance of managing hazardous waste, the knowledge and practice still have scope for improvement. Regular monitoring and training are required at all levels for the management of hazardous dental wastes. Waste management program should be a part of academic curriculum and continuing dental education.